No lar sem coroa: o tempo invadido, a informação rarefeita (estudo da relação das empregadas domésticas com a informação e a leitura) - Marta Pinheiro Aun (1993)
This study examines the role of information poverty in the lives of women who work as domestic servants in Belo Horizonte, Brazil. These women, whether unionised or not, live in the homes of their opression and social exclusion, which starts in childhood as a result of gender and results in their disenfranchisement from society. Acess to information is analysed by gender and social exclusion, is also examined. Data collection's carried out using an interview technique. The results verify that both submision by gender and social exclusion are a result of the relationship between the sexes as a means of maximising profit to accumulate wealth. A major factor influencing this informtion poverty results from these women starting work while still children.